2005
DOI: 10.1007/bf03030409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NaCl stress on germination, antioxidant responses, and proline content in two rice cultivars

Abstract: We investigated the physiological and biochemical bases for salt tolerance in two rice (Oryza sativa L.) cultivars --rel. atively salt-tolerant ~Dongjin ~ and salt-sensitive 'Kumnam'. Salinized hydroponic cultures were studied at the germination and seedling stages. NaCI inhibited germination more severely in 'Kumnam' than in 'Dongjin'. Increasing the salt concentration also deterred growth to a larger extent in the former. Moreover, the leaves of ~Kumnam' exhibited greater increases in lipid peroxidation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 36 publications
(48 reference statements)
2
9
0
Order By: Relevance
“…Also, Jamil et al (2007), mentioned that using NaCl at concentrations between 4.7 to 14.1 dSm -1 inhibited seed germination and seedling growth of two varieties of cabbage. Young et al (2005) and Zhao et al (2009). Also, the current results revealed a pronounced genotypic differences with regard to radical and plumule length.…”
Section: Wwwccsenetorg/jassupporting
confidence: 62%
“…Also, Jamil et al (2007), mentioned that using NaCl at concentrations between 4.7 to 14.1 dSm -1 inhibited seed germination and seedling growth of two varieties of cabbage. Young et al (2005) and Zhao et al (2009). Also, the current results revealed a pronounced genotypic differences with regard to radical and plumule length.…”
Section: Wwwccsenetorg/jassupporting
confidence: 62%
“…Similar results were reported by Islam and Karim [30] who showed that eight genotypes of Thai and Bangladesh rice (Awned-1, Rajbhog-2, Khorina, Soloi, Nonasail, Patnai 23, Sadamota and Chapali) had 80-90% germinationin 160 mM NaCl. Sohn et al [31] reported that the germination percentage of rice cv. Kumnam was completely inhibited at 360 mM NaCl.…”
Section: Discussionmentioning
confidence: 99%
“…Salt causes harmful effects on crop plants by generating or accumulating ROS that leads to disturbance of cellular homeostasis, followed by oxidative stress [14,39,43]. There are many reports that ROS generated from salt stress causes problems in the metabolism of chloroplasts [3,22,40].…”
Section: Discussionmentioning
confidence: 99%